Touch detection of neonatal hypothermia in Nepal. Issue 5 (21st August 2006) - Ellis, M; Manandhar, D; Hunt, L; Barnett, S; Azad, K
Abstract : The use of touch by health workers to detect hypothermia was examined in 250 newborns in Nepal. Palpation of the feet shows fair interobserver agreement (κ = 0.4–0.7) and high sensitivity (>80%) but low specificity (36%–74%) compared with axillary thermometry. Traditional birth attendants should feel an infant's feet to detect hypothermia.